2012
DOI: 10.1155/2012/396019
|View full text |Cite
|
Sign up to set email alerts
|

Free Education in Rwanda: Just One Step towards Reducing Gender and Sibling Inequalities

Abstract: In 2003, Rwanda introduced free education as part of government policy to improve school enrolment in general and the attendance of deprived children in particular. However, in addition to school fees, other factors hamper school careers of children. Shifts in attendance were analysed using binary logistic regression on data from the 2000 and 2005 Integrated Household Living Conditions Surveys. The results show that although the policy has been very successful, the objective has not been achieved. We find a st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…This practice of learning in this school is consistent with free education programs in general. The aim of free education is not just moral goodness to increase APS, but also to support development in terms of economic growth (Lucas & Mbiti 2012, Nkurunziza et al 2012). An adequate number of workers is needed to realize this, and free education is expected to supply new workers.…”
Section: Curriculum and Normalization Of Workersmentioning
confidence: 99%
See 1 more Smart Citation
“…This practice of learning in this school is consistent with free education programs in general. The aim of free education is not just moral goodness to increase APS, but also to support development in terms of economic growth (Lucas & Mbiti 2012, Nkurunziza et al 2012). An adequate number of workers is needed to realize this, and free education is expected to supply new workers.…”
Section: Curriculum and Normalization Of Workersmentioning
confidence: 99%
“…Access to education levels, graduation rates, participation in primary education, and participation based on gender are positively related to increasing primary education assistance fund. Moreover, free education has been proven to increase social equality in a society based on fundamental human rights (Lucas & Mbiti 2012, Nkurunziza et al 2012.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, this excitement the students are showing about using tablet computers also provides a key opportunity to empower young women ( Figure 5). Girls and young women are groups that has received particular close attention from the Government of Rwanda as an educational priority due to long standing Rwandan cultural and social issues that have disadvantaged educational access for girls and young women [13,14]. Thus, our research efforts at building spatial thinking skills through tablet-based geoICTs such as Iwacu provide a key opportunity for accessing these segments of Rwandan society.…”
Section: My Future Plans After Finishing My Secondary School Is To Comentioning
confidence: 99%
“…This raises a wider concern that not everyone benefits from education as a development path, which has also been forcibly expressed for India by Corbridge et al (2013) and Drèze and Sen (2013). Nkurunziza et al (2012) found for Rwanda, that despite improvements, in particular children from very poor and from large households had lower chances of educational enrolment up to 2006. More generally it turned out that Rwanda’s development policy was less suited to target the very poor (Ansoms, 2008).…”
Section: Introductionmentioning
confidence: 96%